Attenuated humoral response against SARS‐CoV‐2 mRNA vaccination in allogeneic stem cell transplantation recipients. Issue 2 (9th October 2022) - Toya, Takashi; Atsuta, Yuya; Sanada, Takahiro; Honda, Tomoko; Sadato, Daichi; Sekiya, Noritaka; Kogure, Hiroko; Takakuwa, Sonomi; Onai, Daishi; Shingai, Naoki; Shimizu, Hiroaki; Najima, Yuho; et al.
Abstract: Antibody persistence several months after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) mRNA vaccination in allogeneic stem cell transplantation recipients remains largely unknown. We sequentially evaluated the humoral response to two doses of mRNA vaccines in 128 adult recipients and identified the risk factors involved in a poor response. The median interval between stem cell transplantation and vaccination was 2.7 years. The SARS‐CoV‐2 S1 Ab became positive after the second vaccination dose in 87.6% of the recipients, and the median titer was 1235.4 arbitrary units (AU)/ml. In patients on corticosteroid treatment, the corticosteroid dose inversely correlated with Ab titer. Multivariate analysis identified risk factors for poor peak response such as an interval from stem cell transplantation ≤1 year, history of clinically significant CMV infection, and use of >5 mg/day prednisolone at vaccination. Six months after vaccination, the median titer decreased to 185.15 AU/ml, and use of >5 mg/day prednisolone at vaccination was significantly associated with a poor response. These results indicate that early vaccination after stem cell transplantation (<12 months) and CMV infection are risk factors for poor peak response, while steroid use is important for a peak as well as a persistent response. In conclusion, although humoral response is observed in many stem cell transplantation recipients after two doses of vaccination, Ab titers diminish with time, and factors associated with persistence and a peak immunity should be considered separately. Abstract : Humoral responses to two doses of SARS‐CoV‐2 mRNA vaccines were sequentially evaluated in 128 allogeneic stem cell transplant recipients. Antibody titers diminish with time, and factors associated with persistence and a peak immunity should be separately counted.